Methods of data analysis for the ball cratering test on TiN and DLC coated steel - Silva, W. M. [UNESP]; Souza, P. S.; Carneiro, J. R. (FapUNIFESP (SciELO), 2016)
Titanium nitride (TiN) coatings are widely used in machining because of its mechanical characteristics which modify the surface of the substrate increasing the capacity of load support and reduction of friction, while a coating as diamond-like carbon (DLC), which also has interesting mechanical properties, needs better attention. In this sense, the development of new coatings such as DLC is as important as wear analysis techniques. This work discusses the methods available to assess abrasive wear of coatings. For this, it has been used the data of the crater volume formed in ball cratering test and compared the difference between the specific wear coefficients of substrate and coating (ks and kc). These coefficients depend of the methods used for data analyses, thus, it has been used four equations to calculate ks and kc. Moreover, profilometry (pf) has been used to calculate the volumes, and thus ks and kc. Also, the roughness of the coatings, the thickness, the images corresponding to the crater formed, the coefficient of friction, the data obtained in wear tests due to the volume removed and, in the end, a comparison between ks and kc by different methods of data analyzes are presented.
Keywords: Ball cratering; Coating; Diamond-like carbon; TiN; Wear